The Influence of Integrated Reporting and ESG Risk on Sustainable Development Goals in LQ45 Index Companies for the 2020-2022 Period - Devina Pauline Samosir; Liza Alvia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the influence of integrated reporting and ESG risks on sustainable development goals in companies listed in the LQ45 index for the 2020-2022 period. This research method uses a quantitative approach by collecting data from financial reports and company sustainability reports. Integrated reporting is measured using indicators of integrated reporting elements and ESG risks are taken based on risk assessments related to the environment, social and corporate governance published by the IDX in collaboration with Morningstar Sustainalytics. The sampling method used purposive sampling and 36 companies were observed within 3 years so that the resulting data was 108. The results of this research show that integrated reporting has a significant positive influence on sustainable development goals. However, ESG risks have no effect on sustainable development goals. Therefore, companies need to implement integrated reporting practices in contributing to the SDGs.